HOME CARE NURSES’ WORK AND FAMILY: IS IT EFFECTIVE FOR NURSING TO FULFILL A FAMILY ROLE? - Yamaguchi, Yoshiko; Inoue, Takahiro (LIFE: International Journal of Health and Life-Sciences, 2017)
Aim: the purpose of this study was to examine whether home care nurses consider that fulfilling a family role makes a positive difference on nursing performance, and to identify associated factors. Methods: a self-report questionnaire was used to survey 236 home care nurses working in Japan. We asked each respondent to identify his/her family-related and work-related variables. We then measured their level of work-family conflict, and the degree to which fulfilling their family role had a positive effect on nursing performance. Descriptive statistics and a hierarchical regression analysis were conducted (p < .05). Results: a total of 201 participants (85.2%) indicated that fulfilling a family role had a positive effect on nursing performance. This perception was positively associated with having a child (β = .248, p = .02) and training in a home healthcare office (β = .154, p = .018). However, age (β = -.225, p = .003), on-call duty (β = -.300, p = .006), and work-family conflict (family interference with work; β = -.206, p = .01) were negatively related to it. Conclusion: the majority of home care nurses perceived that fulfilling a family role had a positive effect on nursing performance. Home care nurses recognized that their experience in childrearing fosters their nursing ability. Future research should explore the skills home care nurses acquire by fulfilling a family role.